2019
DOI: 10.1038/s41374-018-0139-z
|View full text |Cite
|
Sign up to set email alerts
|

First trimester placental endothelial cells from pregnancies with abnormal uterine artery Doppler are more sensitive to apoptotic stimuli

Abstract: Failure of the placental capillary network to develop normally is associated with early onset fetal growth restriction (FGR) and pre-eclampsia (PE). Although the symptoms are observed at term, the problem begins in the first trimester. However, investigations at this clinically relevant time are hindered by difficulties in identifying earlystage pregnancies that are at risk of developing FGR/PE. Using uterine artery Doppler ultrasound in the first trimester as a proxy measure of poor placentation, we have iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…However, more recent evidence has demonstrated that uterine artery Doppler waveforms better reflect maternal systemic vascular resistance rather than local uterine artery resistance (Kalafat et al 2018;Perry et al 2018c). The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round -a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al 2015;Wallace et al 2015;James-Allan et al 2018;Charolidi et al 2019).…”
Section: Preconceptional Subclinical Cardiovascular Dysfunction Predisupporting
confidence: 68%
“…However, more recent evidence has demonstrated that uterine artery Doppler waveforms better reflect maternal systemic vascular resistance rather than local uterine artery resistance (Kalafat et al 2018;Perry et al 2018c). The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round -a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al 2015;Wallace et al 2015;James-Allan et al 2018;Charolidi et al 2019).…”
Section: Preconceptional Subclinical Cardiovascular Dysfunction Predisupporting
confidence: 68%
“…Several studies have shown that placental tissues obtained from women with high-resistance uterine artery Doppler indices were more sensitive to apoptotic stimuli than placental tissue from women with normal indices [8,9,10]. Charolidi et al examined the effect of tumor necrosis factor alpha (TNFα) on placental endothelial cell (PEC) apoptosis in the context of high vs. normal uterine artery Dopplers (Figure 1).…”
Section: Uterine Artery Doppler Indices and Trophoblast Biologymentioning
confidence: 99%
“…Charolidi et al examined the effect of tumor necrosis factor alpha (TNFα) on placental endothelial cell (PEC) apoptosis in the context of high vs. normal uterine artery Dopplers (Figure 1). They demonstrated that placental endothelial cells (PECs) from the high resistance index (RI) group exposed to TNFα had a 40% reduction in half-life compared to those from the normal RI group which were exposed to TNFα [10].…”
Section: Uterine Artery Doppler Indices and Trophoblast Biologymentioning
confidence: 99%
“…Placental vasculature is critically important for proper functioning of the placenta, and depends on the development of vessels beneath the trophoblast layer. These vessels are formed from endothelial cells (EC) that derive from the chorionic mesoderm [ 9 ]. Encompassing the mesenchymal core is a thick trophoblast (TB) epithelial cell layer, which displays a hypomethylated profile [ 10 ].…”
Section: Introductionmentioning
confidence: 99%